2022
DOI: 10.1002/iid3.701
|View full text |Cite
|
Sign up to set email alerts
|

The potential link between Covid‐19 and multiple myeloma: A new saga

Abstract: Background Covid‐19 is considered a primary respiratory disease‐causing viral pneumonia and, in severe cases, leads to acute lung injury and acute respiratory distress syndrome (ARDS). In addition, though, extra‐pulmonary manifestations of Covid‐19 have been shown. Furthermore, severe acute respiratory distress syndrome coronavirus type 2 (SARS‐CoV‐2) infection may coexist with several malignancies, including multiple myeloma (MM). Methods This critical literature revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 141 publications
(372 reference statements)
0
2
0
Order By: Relevance
“…This is consistent with findings from a series of case reports where, among five MM patients with COVID-19, three individuals died due to progressive hypoxemic respiratory failure and one patient developed ARDS following temporary improvement [54]. ARDS is known to develop secondary to MM itself, characterized by diffuse alveolar infiltration by atypical plasma cells [55]. This is preceded by a gradual increase in respiratory failure due to diffuse alveolar metastatic calcification of the alveolar walls and blood vessels, accumulation of alveolar paraproteins, and amyloidosis of alveolar septa [56].…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with findings from a series of case reports where, among five MM patients with COVID-19, three individuals died due to progressive hypoxemic respiratory failure and one patient developed ARDS following temporary improvement [54]. ARDS is known to develop secondary to MM itself, characterized by diffuse alveolar infiltration by atypical plasma cells [55]. This is preceded by a gradual increase in respiratory failure due to diffuse alveolar metastatic calcification of the alveolar walls and blood vessels, accumulation of alveolar paraproteins, and amyloidosis of alveolar septa [56].…”
Section: Discussionsupporting
confidence: 91%
“…It has been recently reported that the expression of angiogenic factors and glutamine deficiency could link COVID-19 severity and MM in the pathogenesis of thrombotic and other cardiovascular complications [ 43 ]. Furthermore, a longer time to respiratory deterioration after SARS-CoV-2 infection, compared to non-hematological subjects, also predicts mortality in MM patients, which suggests that prolonged clinical monitoring may be needed [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…[135] Indeed, Nrf2/HO-1/NQO1 axis is highly activated in the endothelial cells subjected to AGEs activators to provide an adaptive response against OS and/or inflammatory reactions in diabetes. [79,[136][137][138] An experimental study demonstrated that some herbal medicine like Eucommia ulmoides attenuates glucotoxicity by inhibiting AGEs through enhancement of the Nrf2 pathway in diabetic mice. [139] These findings proposed the potential anti-inflammatory effects of Nrf2 through inhibition expression of mTOR, AGEs, NF-κB, and NLRP3 inflammasome.…”
Section: Nrf2 Role In Inflammation and Immune Responsementioning
confidence: 99%